TRANSMITTING RESEARCH FINDINGS INTO FARM PRACTICE - Frame, J. (Pastos, 2011)
When adapted and applied to farm practice, scientific research findings are a valuable ’resource’. There are many methods of technology or knowledge transfer and farmers have to be selective in choosing which method or methods suit their particular circumstances. Clearly, personal contact with advisers or consultants and discussions with fellow farmers are effective and preferred methods. The written word, provided it is couched in non-scientific and simple language, is also effective. It is foreseen that the use of decisión support models set up on the internet will expand as a computer literate generation of younger farmers take up the farming reins. In effect, the internet represents a revolution in communication. Nevertheless, personal contact will remain the acmé (now expensive) of farming advice provisión together with monitor farm discussion groups. Increasingly and rightly so, farmers are participating along with researchers and advisers in official development farms or in commercial pilot or monitor farms that demónstrate improved systems of management and production. National and local agricultural sector societies also play a major role in technology transfer through their meetings, publications and the interaction of their members drawn from various agricultural professions. Research institutes have had to incorpórate a technology transfer component into their grant-aided research projects. Agriculture has become multifunctional, having had to graft on a host of legislated non-production-orientated activities involving improvement of the environment and the landscape for example. Thus research and development and associated knowledge transfer provisión have had to be adapted to meet to the new circumstances.